Report of Group on Seismology - Planning Commission (Planning Commission, 1972)
The 1972 Report on Seismology by the Government of India outlines a comprehensive strategy to strengthen seismological research and infrastructure in the country. Initiated to enhance data collection, monitoring, and utilization, the report emphasizes the importance of establishing a national network of observatories, adopting advanced instrumentation, and promoting inter-institutional collaboration. Key findings highlight seismic impacts on infrastructure, limitations of the existing observatory network, and the need for centralized management and data dissemination. Recommendations include expanding the network to 100+ stations, developing local instruments, establishing a Central Institute and Data Center, and enhancing consultancy services. Implementing these measures is projected to improve earthquake preparedness, disaster mitigation, and infrastructure resilience, while fostering scientific research and economic benefits.
Government of India Planning Commission New Delhi 1972
Government of India Planning Commission New Delhi 1972
Keywords: Seismology; Earthquake Monitoring; National Network; Observatories; Data Management; Infrastructure Resilience; Instrumentation; Research Collaboration; Seismic Risk Assessment; Central Institute